The NLRP3 Inflammasome Renders Cell Death Pro-inflammatory. Issue 2 (19th January 2018) - Gaidt, Moritz M.; Hornung, Veit
Abstract: NLRP3 is the most studied inflammasome sensor due to its crucial involvement in sterile and infection-triggered inflammation. Although its molecular mode of activation remains to be defined, it is well established that low intracellular potassium concentrations result in its activation. This functionality allows the classical NLRP3 pathway to serve as a highly sensitive, but non-specific surveillance mechanism responding to any type of perturbation that breaches plasma membrane integrity and the associated potassium gradient across the membrane. Here, we review our current knowledge on potassium efflux-dependent NLRP3 activation, with a special focus on how major cell death programs are rendered pro-inflammatory by secondary NLRP3 activation. Apart from the "alternative inflammasome" as the major exception to the rule, this connection explains the fundamental importance of NLRP3 in cell death-associated inflammation and firmly establishes NLRP3 as a principal surveillance mechanism of cellular integrity. Graphical abstract: Highlights: NLRP3 is activated by low intracellular potassium levels. This pathway serves as a surveillance mechanism of plasma membrane integrity. Due to this functionality, major forms of programmed cell death result in secondary NLRP3 activation.